2021
DOI: 10.1097/bpo.0000000000001998
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Acquisition of Lower Extremity Braces in the Pediatric Orthopaedic Population

Abstract: Background: Lower extremity brace-wear compliance has been studied in pediatrics, but failure to acquire a prescribed brace has not been included. The purpose of this study was to evaluate brace acquisition as a component of brace-wear compliance. Methods: Records of patients (0 to 21 y) prescribed lower extremity braces from 2017 to 2019 were reviewed. Diagnoses included cerebral palsy, spina bifida, short Achilles tendon, clubfoot, and other. Brace type was categorized as clubfoot foot abduction orthosis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…15 A 2022 study found that non-white patients who were prescribed a brace were significantly less likely to actually receive the brace compared to white children. 16 Perhaps one of the most important studies on bias within pediatric orthopaedic surgery is a 2002 study published in JAMA on rates of reporting suspected child abuse among children with fractures. 17 In this study, charts were retrospectively reviewed by a reviewer blinded to the child's race or ethnicity and determined likelihood of abuse.…”
Section: Health Equity In Orthopaedic Surgery Todaymentioning
confidence: 99%
“…15 A 2022 study found that non-white patients who were prescribed a brace were significantly less likely to actually receive the brace compared to white children. 16 Perhaps one of the most important studies on bias within pediatric orthopaedic surgery is a 2002 study published in JAMA on rates of reporting suspected child abuse among children with fractures. 17 In this study, charts were retrospectively reviewed by a reviewer blinded to the child's race or ethnicity and determined likelihood of abuse.…”
Section: Health Equity In Orthopaedic Surgery Todaymentioning
confidence: 99%